Respiratory Travel Medicine - Ni Wayan Candrawati (Faculty of Medicine Universitas Airlangga, 2022)
International tourist arrivals continue to increase over time due to global economic growth, increasing middle class in developing countries, technological advances, innovative business concepts, cost-effective travel, and facilitation of visas. The increase in tourist visits has resulted in health problems due to the trips. Respiratory tract infections are the main reason tourists seek medical care. Respiratory infections occur in 20% of all tourists, almost the same as the incidence of diarrhea. The majority of international inbound tourism involved air travel. Though physiological changes happen in everyone while air travel, people with lung disease are at high risk for significant complications and necessitate a specific risk assessment strategy. A pre-flight evaluation is conducted if there is any uncertainty regarding the patient's fitness for flight and the effect of eligibility to fly. This literature review summarized the important aspect of travel medicine from the respiratory medicine point of view.